Answer:
m = 9
Explanation:
Using the rules of exponents
=
![a^(mn)](https://img.qammunity.org/2022/formulas/mathematics/high-school/cmsd2gfv2pql9zrvq0ifgu4i63g47fufzy.png)
×
⇔
![a^((m+n))](https://img.qammunity.org/2022/formulas/mathematics/high-school/lvxfgxjnyl8zw0q7pmgf8j4nu0n72zdom1.png)
=
![(1)/(a^(m) )](https://img.qammunity.org/2022/formulas/mathematics/high-school/e1r20dpy202g477s06snp5tj53atrfb6c6.png)
Then
×
= 243 ← express all values to base 3
×
=
![3^(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/u8fg3rhm9nemxtfnw6akd21adt47rj7nj9.png)
×
=
![3^(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/u8fg3rhm9nemxtfnw6akd21adt47rj7nj9.png)
×
=
![3^(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/u8fg3rhm9nemxtfnw6akd21adt47rj7nj9.png)
=
Since bases on both sides are equal, both 3 , then equate exponents
- 3m - 4 = 5 ( add 4 to both sides )
- 3m = 9 ( divide both sides by - 3 )
m = - 3